Cardiopulmonary function and intestinal blood flow in anaesthetised, experimentally endotoxaemic horses given a constant rate infusion of dexmedetomidine. (30th September 2021) - Hector, Rachel C.; Rezende, Marlis L.; Nelson, Brad B.; Monnet, Eric
Abstract: Background: Endotoxaemia causes untoward inflammatory‐mediated effects that might be attenuated by dexmedetomidine. Objectives: To evaluate the effects of a dexmedetomidine intravenous (IV) infusion on systemic and intestinal haemodynamics and arterial blood gas values in sevoflurane‐anaesthetised horses administered Escherichia coli O55:B5 lipopolysaccharides (LPS). Study design: Randomised controlled in vivo experiment. Methods: A total of 13 horses weighing 456 ± 86 kg (mean ± standard deviation) and aged 13.9 ± 9.0 years donated for euthanasia underwent ventral midline celiotomy using sevoflurane anaesthesia. Baseline physiological variables were recorded after a 90‐minute equilibration period. All horses were given 0.1 mcg/kg bwt LPS IV. Horses were randomly assigned to no further treatment (group LPS; seven horses) or IV administration of dexmedetomidine (loading dose 1.75 mcg/kg bwt followed by 1.75 mcg/kg bwt/h; group LPS–Dex; six horses) with concurrent target sevoflurane dose reduction of 50%. Cardiac index (CI; thermodilution), intestinal blood flow, arterial blood parameters and plasma dexmedetomidine concentration measurements were recorded every 30 minutes until euthanasia at 390 minutes. Data were compared between and within groups to baseline using a mixed model analysis (significance P < .05). Results: In LPS‐Dex horses, intestinal blood flow and CI were transiently decreased after the dexmedetomidine loading dose, but no significant differences were found compared with baseline during the infusion. Sevoflurane dose was reliably reduced by approximately 40%. Significant differences were identified in creatinine (115 umol/L LPS‐Dex; 195 umol/L LPS), bicarbonate (29.7 mmol/L LPS‐Dex; 23 mmol/L LPS) and base excess (2.0 mmol/L LPS‐Dex; −5.3 mmol/L LPS). Dexmedetomidine plasma concentrations were highest after the loading dose and stable during infusion dosing. Main limitations: Experimental conditions are not reflective of clinical colic management. Conclusions: A dexmedetomidine infusion with sevoflurane dose reduction attenuated some deleterious changes in anaesthetised horses administered LPS without sustained negative cardiovascular effects and may be beneficial during colic surgery.